January - September, 1997 (Hoboken (N.J.), 1997)
Citations with abstracts to worldwide literature in engineering and technology, excluding patents
Keywords: Công nghệ,Kỹ thuật,Engineering,Technology; Tóm tắt,Tóm tắt,Abstracts,Abstracts